The role of heterogenous environmental conditions in shaping the spatiotemporal distribution of competing Aedes mosquitoes in Panama: implications for the landscape of arboviral disease transmission (2020)
Monitoring the invasion process of the Asian tiger mosquito Aedes albopictus and its interaction with the contender Aedes aegypti, is critical to prevent and control the arthropod-borne viruses (i.e., Arboviruses) they transmit to humans. Generally, the superior ecological competitor Ae. albopictus displaces Ae. aegypti from most geographic areas, with the combining factors of biology and environment influencing the competitive outcome. Nonetheless, detailed studies asserting displacement come largely from sub-tropical areas, with relatively less effort being made in tropical environments, including no comprehensive research about Aedes biological interactions in Mesoamerica. Here, we examine contemporary and historical mosquito surveillance data to assess the role of shifting abiotic conditions in shaping the spatiotemporal distribution of competing Aedes species in the Republic of Panama. In accordance with prior studies, we show that Ae. albopictus has displaced Ae. aegypti under suboptimal wet tropical climate conditions and more vegetated environments within the southwestern Azuero Peninsula. Conversely, in the eastern Azuero Peninsula, Ae. aegypti persists with Ae. albopictus under optimal niche conditions in a dry and more seasonal tropical climate. While species displacement was stable over the course of two years, the presence of both species generally appears to fluctuate in tandem in areas of coexistence. Aedes albopictus was always more frequently found and abundant regardless of location and climatic season. The heterogenous environmental conditions of Panama shape the competitive outcome and microgeographic distribution of Aedes mosquitoes, with potential consequences for the transmission dynamics of urban and sylvatic zoonotic diseases.